Early Warning System for Potential Fires in the Dry Season Based on the Internet of Things - Maitimu, Excel Barthel; Widiasari, Indrastanti Ratna (International Journal of Natural Science and Engineering, 2022)
Almost every year, forest and land fires occur in Indonesia, the impact of which is felt by the surrounding community and neighboring countries. Such as the recent fires in East Kotawaringin and Katingan, Central Kalimantan. The land affected by the fire is believed to be a concession belonging to a Malaysian company. According to the Ministry of Environment and Forestry, the area of forest and land fires is calculated based on an analysis of Landsat 8 OLI/TIRS satellite imagery, which is compared (overlay) with data on the distribution of hotspots. In this research, the Internet of Things (IoT) can be useful in preventing forest fires that usually occur on the slopes of Merbabu during the dry season. IoT sensor technology can detect air humidity, temperature, and wind speed parameters for fires in the dry season. This study aims to warn of potential forest and land fires in Mount Merbabu by providing notifications from IoT sensors. From the sensor testing that has been done, it can be seen that the sensor can provide information accurately and in real-time. The tests were carried out in three places: at the foot of Mount Merbabu, the SWCU FTI Peak, and the rice fields. The different results in three places with different vegetation indices indicate that the design of a fire potential warning system based on the Internet of Things in the dry season (July – September) can be used in areas with a low vegetation index on the slopes of Mount Merbabu, the majority of which are dry and easy grasslands burnt.